2009
DOI: 10.1091/mbc.e08-05-0456
|View full text |Cite
|
Sign up to set email alerts
|

Roles of BLOC-1 and Adaptor Protein-3 Complexes in Cargo Sorting to Synaptic Vesicles

Abstract: Neuronal lysosomes and their biogenesis mechanisms are primarily thought to clear metabolites and proteins whose abnormal accumulation leads to neurodegenerative disease pathology. However, it remains unknown whether lysosomal sorting mechanisms regulate the levels of membrane proteins within synaptic vesicles. Using high-resolution deconvolution microscopy, we identified early endosomal compartments where both selected synaptic vesicle and lysosomal membrane proteins coexist with the adaptor protein complex 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(133 citation statements)
references
References 91 publications
5
126
0
2
Order By: Relevance
“…The type II PI4Ks were implicated in transferrin receptor endocytosis and recycling (83), and PI4KII␣ has a major role in EGF receptor degradation in the late endosomal pathway (1060). Recent studies showed that knock-down of type II PI4K␣ causes enlargement of prelysosomal/lysosomal compartments (298, 741,1128), and PI4K␣ is required for lysosomal delivery of the Gaucher disease enzyme ␤-glucocerebrosidase and its receptor, LIMP-2 (741). It will be important to understand where and how the PtdIns4P to PtdIns3P switch happens in the various endocytic compartments.…”
Section: The Role Of Ptdins4p In Endomembranesmentioning
confidence: 99%
“…The type II PI4Ks were implicated in transferrin receptor endocytosis and recycling (83), and PI4KII␣ has a major role in EGF receptor degradation in the late endosomal pathway (1060). Recent studies showed that knock-down of type II PI4K␣ causes enlargement of prelysosomal/lysosomal compartments (298, 741,1128), and PI4K␣ is required for lysosomal delivery of the Gaucher disease enzyme ␤-glucocerebrosidase and its receptor, LIMP-2 (741). It will be important to understand where and how the PtdIns4P to PtdIns3P switch happens in the various endocytic compartments.…”
Section: The Role Of Ptdins4p In Endomembranesmentioning
confidence: 99%
“…Thus, if coats are involved, such coats should be different from endocytic clathrin coats. AP-3 and AP-1, heterotetrameric complexes similar to AP-2 that may function independently of clathrin, are potential candidates (Faundez et al 1998;Nakatsu et al 2004;Kim and Ryan 2009;Newell-Litwa et al 2009;Glyvuk et al 2010). However, although both AP-3 and AP-1 were implicated in synaptic vesicle recycling …”
Section: Bulk Endocytosismentioning
confidence: 99%
“…11 Because BLOC-1 and AP-3 regulate SNARE distribution in neurons, [62][63][64] we tested whether these SNARE components were depleted from HPS model platelets. However, levels of each SNARE component were not significantly different in lysates from WT, pearl, pallid, or light ear platelets ( Figure 6E).…”
Section: Hps Platelets Express Normal Levels Of Granule Fusion Proteinsmentioning
confidence: 99%